The Divinities of Umayyah Ibn Abi al-Salt and Sources that Shape the Qur’anic Text: A critical study in the vision of the French orientalist Clement Hauar - Muhammad, Ass. Prof. Dr. Shaheed Karim (Thi Qar Arts Journal, 2022)
The research attempts to investigate the vision of the French orientalist (Clement Hauar) about the sources of the formation of the Qur’anic text in the era of revelation, and he adopted an idea that seemed somewhat different from what the orientalist lesson was familiar with until his era, as he attributed the formation of some of his concepts and ideas to a number of Hanafi poetry in the pre-Islamic era, led by the poet Umayyah Ibn Abi al-Salt, whose poetic stanzas resembled some of the verses of the Qur’anic text. Was the issue as adopted and promoted by Kalman Hawar, or was it completely reversed?